The role of first language transfer in the acquisition of definiteness in specific and generic contexts by Saudi-Arabic learners of English - AFNAN ABORAS (2021)
Studies on the acquisition of definiteness in English by Arabic learners have largely focused on the errors made using articles. The present study investigates the accuracy of Saudi-Arabic learners with regard to the different features associated with definiteness: specificity and genericity. Arabic, like English, contains a definite article and an indefinite article; however, article usage differs between the languages in that Saudi-Arabic tends to drop the indefinite article as it is not obligatory, as it is in English. The purpose of this study is therefore to examine the accuracy with which learners employ specificity and genericity and the effect of the first language on learners’ accuracy. The thesis examines the effects of proficiency level and vocabulary level (receptive and productive). Two experimental studies were carried out, the first focusing on specificity by testing the Bottleneck Hypothesis (Slabakova, 2008) and the Fluctuation Hypothesis (Ionin et al., 2004). The former posits that learners are able to map features between L1 and L2 and that similarities and differences between languages affects acquisition. The latter hypothesis relates to definiteness and specificity, postulating that learners fluctuate between article settings until they acquire the Article Choice Parameter in English. The second experiment focused on genericity with singular and plural contexts, testing the Bottleneck Hypothesis (Slabakova, 2008) and the Representational Deficit Hypothesis (Hawkins & Chan, 1997), which argues that learners cannot acquire a new uninterpretable feature if it is already set in their L1. These experiments demonstrated that the accuracy of Saudi-Arabic learners of English varies according to definiteness features, as the participants performed more accurately with specificity than with genericity. First language transfer affected uses involving genericity more than those involving specificity. The other factors – proficiency level and receptive and productive vocabulary knowledge – affected the learners’ accuracy with respect to both specificity and genericity.